Источники и последствия укорененности для экономической эффективности организаций: влияние сетей - UzziBrian (Journal of Economic Sociology, 2010)
Additionally to the dispute on social embededness of economic action the author tries to operationalize it and disclose in what way the embedded ties contribute to more effective economy in comparison to the casual market ties. The paper provides an empirical test of the embededness meaning for economic success. At the end of the paper you can find the empirical tests for the hypotheses and concluding remarks.